Implementation of SAK EMKM as the Basis for Annual Tax Reporting - Koerniawan Dwi Wibawa; Dewi Kirowati; Tri Septianto; Ahmad Kudhori; Ghea Fauziah; Sebti Nurkumalasari; Ika Rahuli Kusuma Dewi (Pascasarjana Universitas Mataram, 2025)
This community service activity aimed to enhance the understanding and practical skills of Grade XII Accounting students at SMK Negeri 1 Geger in applying the Financial Accounting Standards for Micro Small and Medium Enterprises (SAK EMKM) as the basis for annual tax reporting. Conducted on September 2 2025 the in person program covered four key topics the role of MSMEs in the national economy components of SAK EMKM based financial statements transaction recognition methods and simplified tax calculation approaches. Through a combination of socialization hands on Excel based financial statement preparation and interactive discussions participants’ demonstrated improved comprehension of SAK EMKM principles journal entries and basic tax computation. Although challenges remain particularly in grasping abstract accounting concepts such as cost of goods sold depreciation and liability classification the activity successfully laid a foundational framework for future competency development. The use of Microsoft Excel proved effective for automation yet highlighted the need for technical guidance to avoid errors. This initiative underscores the importance of integrating SAK EMKM into vocational accounting education to produce job ready graduates who can support transparent accountable and tax compliant financial management in Indonesias MSME sector. Continued mentoring and collaboration between educational institutions and stakeholders are recommended to sustain and expand these outcomes.